Cerebrospinal fluid markers reveal intrathecal inflammation in progressive multiple sclerosis. Issue 1 (16th April 2015) - Komori, Mika; Blake, Andrew; Greenwood, Mark; Lin, Yen Chih; Kosa, Peter; Ghazali, Danish; Winokur, Paige; Natrajan, Muktha; Wuest, Simone C.; Romm, Elena; Panackal, Anil A.; Williamson, Peter R.; et al.
<x xml:space="preserve">Abstract</x> Objective The management of complex patients with neuroimmunological diseases is hindered by an inability to reliably measure intrathecal inflammation. Currently implemented laboratory tests developed >40 years ago either are not dynamic or fail to capture low levels of central nervous system (CNS) inflammation. Therefore, we aimed to identify and validate biomarkers of CNS inflammation in 2 blinded, prospectively acquired cohorts of untreated patients with neuroimmunological diseases and embedded controls, with the ultimate goal of developing clinically useful tools. Methods Because biomarkers with maximum utility reflect immune phenotypes, we included an assessment of cell specificity in purified primary immune cells. Biomarkers were quantified by optimized electrochemiluminescent immunoassays. Results Among markers with cell‐specific secretion, soluble CD27 is a validated biomarker of intrathecal T‐cell activation, with an area under the receiver operating characteristic curve of 0.97. Comparing the quantities of cerebrospinal fluid (CSF) immune cells and their respective cell‐specific soluble biomarkers (released by CSF cells as well as their counterparts in CNS tissue) provided invaluable information about stationary CNS immune responses, previously attainable via brain biopsy only. Unexpectedly, progressive and relapsing–remitting multiple sclerosis (MS) patients have comparable numbers of activated intrathecal T and B cells, which are preferentially embedded in CNS tissue in the former group. Interpretation The cell‐specific biomarkers of intrathecal inflammation may improve diagnosis and management of neuroimmunological diseases and provide pharmacodynamic markers for future therapeutic developments in patients with intrathecal inflammation that is not captured by imaging, such as in progressive MS. Ann Neurol 2015;78:3–20